Analysis of the Effectiveness of the General Election Commission's Socialization as a Media for Political Education to Create a Democratic Society - Wandi Subroto (International Journal of Science and Society, 2021)
The purpose of this study was to analyze the effectiveness of the socialization program carried out by the General Elections Commission as a medium of political education for the community. This study uses a type of juridical-normative research. The sources of law used in this study are secondary and tertiary sources of law. Sources of data were collected using questionnaires, interviews and literature studies. The location of this research was carried out at the General Election Commission office in Palembang. The data analysis method used in this study is a qualitative method which was collected during the research. The research respondents were 50 people who were selected using purposive sampling method. To maintain the validity of the data, field observation techniques and data triangulation techniques were used. Based on the results of the research data, it can be concluded that the socialization carried out by the General Election Commission of the city of Palembang was quite effective. This is supported by the strategy used, namely holding a political discussion forum, building an Election Smart House and carrying out direct outreach to novice voters who are in high school or equivalent, as well as two-way communication conducted by the General Election Commission of the city of Palembang.